Petroleum as a space for non-translation: Hikmet, Negarestani, Parshchikov - Kirill M. Korchagin (Слово.ру: балтийский акцент, 2023)
In 1927, Nâzım Hikmet composed several poems based on his impressions of his visit to Azerbaijani capital, the city of Baku. They will be included in the collection Song of the Sun-drinkers (1928) and will soon be translated into Russian. The Baku cycle was one of the first attempts at a symbolic representation of petroleum in Russian poetry, in many ways foreshadowing the later poetics of the subject, which will develop on Russian material only in the 2000s. One can look at these poems by Hikmet as one of the first attempts to create a philosophy of petroleum, which will find its most large-scale embodiment in the philosophical novel “Cyclonopedia” by Reza Negarestani, where petroleum constitutes a new type of subjectivity, simultaneously fluid and explosive. On the other hand, the image of petroleum will play a key role in Alexei Parshchikov’s poem of the same name, where one can also discern echoes of this philosophy in Hikmet’s Baku cycle. For all these authors, petroleum acts as a radical expression of the logic of non-translation: it is a condensed memory of antiquity, which cannot be directly accessed; its mystery cannot be revealed because, in a sense, it contains no mystery. Such a paradoxical semiotics leads all three authors to the idea that petroleum is alien to the human world and has a special inhuman agency.